On Organizing and Supervising the Independent Work of Drawing Geometry Guidelines and General Rules (Texas Journal of Multidisciplinary Studies, 2022)
This article discusses the effectiveness of drawing geometry lessons and ways to increase students' interest in this subject. Also, the methods and game technologies that can be used in the course of the lesson and the organization and control of independent work are shown through examples. It has been shown that it is possible to develop the creative abilities of students through independent education .